Computation of Optimal Cross Section of Gravity Dams Using Genetic Algorithms - Salmasi, Farzin; Abraham, John (Current Overview on Science and Technology Research Vol. 6, 2022)
An interactive method that involves a preliminary layout of the structure, followed by a stability and stress study, is used to construct gravity dams. This study presents a method to define the optimal cross section of gravity dams determined using a genetic algorithm. To solve the optimization task (minimize the cost of the dam), an optimization routine based on genetic algorithms (GAs) was implemented in a Microsoft Excel spreadsheet. It was found to perform well and GA parameters were optimized in a parametric study. Using the parameters found in the parametric study, the top width of an arbitrary gravity dam was found and compared to a gradient-based optimization method (classic method). The agreement between the two approaches was excellent. For an optimal dam cross section, the ratio of the dam base to dam height is \(\sim\) 0.85, and ratio of dam top width to dam height is \(\sim\) 0.13. This computational approach may provide calculations of the optimal top width for a wide range of gravity dam heights.